2017
DOI: 10.3832/ifor2204-010
|View full text |Cite
|
Sign up to set email alerts
|

Seeing trees from space: above-ground biomass estimates of intact and degraded montane rainforests from high-resolution optical imagery

Abstract: Accurately quantifying the above-ground carbon stock of tropical rainforest trees is the core component of "Reduction of Emissions from Deforestation and Forest Degradation-plus" (REDD+) projects and is important for evaluating the effects of anthropogenic global change. We used high-resolution optical imagery (IKONOS-2) to identify individual tree crowns in intact and degraded rainforests in the mountains of Northern Borneo, comparing our results with 50 ground-based plots dispersed in intact and degraded for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…The discretization of the plots according to the negative or positive nature of the β-diversity scores has been reported before, also relating biomass mean values to certain classes [10]. The previous study and other related [11,45] had found a clear link between community taxonomic diversity and carbon stock through patches with human disturbances.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The discretization of the plots according to the negative or positive nature of the β-diversity scores has been reported before, also relating biomass mean values to certain classes [10]. The previous study and other related [11,45] had found a clear link between community taxonomic diversity and carbon stock through patches with human disturbances.…”
Section: Discussionsupporting
confidence: 57%
“…Tree community composition is a key indicator of forest degradation [10,11], because it is one of the last recovering variables after a disturbance [12,13], and consequently it is an excelent measure of diversity loss. Crown-level assessment of species composition has been increasingly successful for boreal and temperate forests [14][15][16], but its applicability remains challenging for the most complex tropical forests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Borneo, above-ground biomass was calculated (Root mean square error (RMSE) = 20.3 tonnes.ha −1 ) by relating stem diameter to crown area. The crown was delineated by segmenting IKONOS images (1 to 4 m-resolution), with a segmentation accuracy of 39% for degraded forests [90]. Good results were also obtained by mixing different types of data, giving both spectral and structural information (optical and aerial LiDAR [91], optical and radar satellite with data saturation beyond 300 Mg.ha −1 [92]).…”
Section: Indicators Of Composition Structure and Regeneration Measured With Remote Sensingmentioning
confidence: 99%
“…Very high-resolution optical data provide better results and opportunities for forest monitoring. They allow the detection of small disturbances (SPOT, WorldView-2, GeoEye-1) [75,153], the boundaries of tree crown on which the biomass depends (SPOT, WorldView-2) [90,154,155], the identification of tree species (WorldView-3) [156,157] or the measurement of biomass in combination with airborne LiDAR measurements (Planet Dove) [158,159]. These data are, however, not free of charge and are still dependent on the very numerous clouds in tropical regions, preventing regular monitoring via satellite data.…”
Section: Remote Sensing Metrics and Indices Used To Detect Tropical Moist Forest Degradationmentioning
confidence: 99%